Predictable invasion dynamics in North American populations of the Eurasian collared dove Streptopelia decaocto. Issue 1862 (6th September 2017) - Ingenloff, Kathryn; Hensz, Christopher M.; Anamza, Tashitso; Barve, Vijay; Campbell, Lindsay P.; Cooper, Jacob C.; Komp, Ed; Jimenez, Laura; Olson, Karen V.; Osorio-Olvera, Luis; Owens, Hannah L.; Peterson, A. Townsend; et al.
Abstract : Species invasions represent a significant dimension of global change yet the dynamics of invasions remain poorly understood and are considered rather unpredictable. We explored interannual dynamics of the invasion process in the Eurasian collared dove ( Streptopelia decaocto ) and tested whether the advance of the invasion front of the species in North America relates to centrality (versus peripherality) within its estimated fundamental ecological niche. We used ecological niche modelling approaches to estimate the dimensions of the fundamental ecological niche on the Old World distribution of the species, and then transferred that model to the New World as measures of centrality versus peripherality within the niche for the species. Although our hypothesis was that the invasion front would advance faster over more favourable (i.e. more central) conditions, the reverse was the case: the invasion expanded faster in areas presenting less favourable (i.e. more peripheral) conditions for the species as it advanced across North America. This result offers a first view of a predictive approach to the dynamics of species' invasions, and thereby has relevant implications for the management of invasive species, as such a predictive understanding would allow better anticipation of coming steps and advances in the progress of invasions, important to designing and guiding effective remediation and mitigation efforts.